2005
DOI: 10.1021/ja0440295
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Recognition of Trigonal Oxyanions Using a Ditopic Salt Receptor:  Evidence for Anisotropic Shielding Surface around Nitrate Anion

Abstract: A ditopic, macrobicyclic receptor with adjacent anion and cation binding sites is able to extract a range of monovalent salts into chloroform solution. The structures of the receptor complexed with KAcO, LiNO(3), NaNO(3), KNO(3), and NaNO(2) are characterized in solution by NMR spectroscopy and in the solid state by X-ray crystallography. The sodium and potassium salts are bound to the receptor as contact ion-pairs, with the metal cation located in the receptor's crown ether ring and the trigonal oxyanion hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0
5

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(64 citation statements)
references
References 31 publications
2
57
0
5
Order By: Relevance
“…Furthermore, the phosphate groups of potato starch effectively hindered penetration of the granules by nitrate anions so they should be situated on the granule surface. This process might be facilitated by formation of hydrogen bonds between nitrate lone pair electrons and hydrogen atoms of -OH groups at the granule surface like those described for nitrate ions and -NH groups (Mahoney et al, 2005). The granule zeta potentials did not change after treatment the starch with CuCl 2 .…”
Section: Influence Of Kind Of Cationsmentioning
confidence: 82%
“…Furthermore, the phosphate groups of potato starch effectively hindered penetration of the granules by nitrate anions so they should be situated on the granule surface. This process might be facilitated by formation of hydrogen bonds between nitrate lone pair electrons and hydrogen atoms of -OH groups at the granule surface like those described for nitrate ions and -NH groups (Mahoney et al, 2005). The granule zeta potentials did not change after treatment the starch with CuCl 2 .…”
Section: Influence Of Kind Of Cationsmentioning
confidence: 82%
“…43 forms strong complexes with trigonal oxyanions, such as NO 3 -and OAc -, as well as with the halide anions. 59 Proton NMR spectral studies provided confirmation that compound which has an additional pyrrole-derived hydrogen bond donor site. Proton NMR spectroscopic titrations revealed that the affinity of ditopic receptor 1.46 for Cl -is three times higher than 1.43.…”
Section: Ion Pair Receptors That Contain Amide Groups For Anion Recogmentioning
confidence: 96%
“…[1][2][3][4][5][6][7][8][9] Recent developments have focused on the recognition of heavy-metal salts such as nickel or copper sulfate for hydrometallurgical applications. [10][11][12] Welldesigned binding sites that combine electrostatic or hydrogen-bonding interactions enable ditopic host molecules to do this.…”
Section: Introductionmentioning
confidence: 99%